Effects of trace minerals source in the broiler breeder diet and eggshell translucency on embryonic development of the offspring - Henry van den Brand; Timo Hubers; Ilona van den Anker; Cibele A. Torres; Emily Frehen; Monique Ooms; Joop Arts; Bjorge F.A. Laurenssen; Marcel J.W. Heetkamp; Bas Kemp; Roos Molenaar (Poultry Science, 2023)
ABSTRACT: In 2 experiments, interactions between trace mineral (Zn, Mn, Cu, Se) source (organic or inorganic) in the broiler breeder diet and egg translucency (high or low) on egg characteristics and embryonic development were investigated. In the first experiment, eggs from old breeders (55–57 wk) and in the second experiment, eggs from prime breeders (34–36 wk) were used. Egg composition and bacterial load on the eggshell were analyzed in fresh eggs. During incubation, metabolic heat production of the embryos (d 8 (E8) to 19 of incubation) and tibia ossification (E8.5–E14.5) were determined daily. At hatch, chicken quality was assessed, including tibia biophysical characteristic. Egg quality was not affected by breeder trace minerals source or egg translucency in both experiments. In both experiments, an interaction between trace minerals source and translucency score was found for egg weight loss during incubation. In inorganic trace minerals fed breeders, a high egg translucency resulted in a higher egg weight loss than a low egg translucency, whereas this difference was not seen in organic trace minerals fed breeders. Embryonic heat production and tibia ossification were not affected by trace minerals source or egg translucency. Chicken quality showed ambiguous results between experiment 1 and 2 regarding trace minerals source in the breeder diet. In experiment 2, high translucent eggs from organic fed breeders hatched later than eggs from the other three treatment groups and additionally, high egg translucency resulted in lower residual yolk weight and higher heart and liver percentage of YFBM compared to low egg translucency. Tibia biophysical characteristics at hatch were not affected by trace minerals source or egg translucency. It can be concluded that organic trace minerals source in broiler breeder diet affects eggshell conductance, particularly in low translucent eggs, but effects on chicken quality and tibia characteristics appears to be limited.